Application of supported electrocatalyst in degrading orange II dye wastewater in three-dimensional electrode system
By using a supported cobalt ferrite/montmorillonite electrocatalyst in a three-dimensional electrode system, combining electric field action and permonosulfate activation, the problem that traditional two-dimensional electrocatalytic systems are difficult to efficiently degrade orange-yellow II dye wastewater, achieving high efficiency pollutant degradation and mineralization effects.
Patent Information
- Application Number
- CN202411729737.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to efficiently degrade difficult-to-degrade organic pollutants such as yellow orange-II dye wastewater through traditional two-dimensional electrocatalytic systems, especially in deep oxidation and mineralization.
The supported electrocatalyst is used to degrade the yellow orange dye wastewater in a three-dimensional electrode system. The cobalt ferrite/montmorillonite electrocatalyst is polarized into particle electrodes, and combined with electric field action and permonosulfate activation, efficient degradation is achieved.
Through the three-dimensional electrode system, cobalt ferrite/montmorillonite electrocatalyst can accelerate the activation of monosulfate to produce active substances, significantly improving the degradation rate and efficiency of the orange-yellow II dye, and realizing deep oxidation and mineralization of pollutants.
Smart Images

Figure CN119390197A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to application of a supported electrocatalyst in a three-dimensional electrode system to degrade orange II dye wastewater. Background Art
[0002] Refractory organic pollutants in water bodies, such as dyes, pose an indirect or direct threat to the human living environment, and their difficult biodegradability further increases their harmfulness. Dyes with azo structures have complex and stable structures and are a type of thorny organic pollutants in water bodies. Orange II, as a typical azo dye, is widely used in the textile and cosmetics industries and has cytotoxicity and genotoxicity. Electrochemical oxidation technology, as a typical advanced oxidation technology for the treatment of organic pollutants, has the characteristics of strong adaptability and easy operation. However, due to the limitation of electrode size, relying solely on anodic oxidation capacity is not enough to achieve deep oxidation and mineralization of organic matter. The advanced oxidation process based on permonosulfate is another popular organic pollutant treatment technology, which can rapidly produce sulfate radicals and other types of active species with strong oxidizing ability through a variety of activation methods. Permonosulfate can be activated by electrical activation and transition metals.
[0003] The typical electro-permonosulfate system consists of a pair of anodes and cathodes and is a traditional two-dimensional electrocatalytic system. In recent years, three-dimensional electrode systems have made good progress in reducing the emission of refractory substances. Compared with flat electrode systems, three-dimensional electrode systems have been proven to be superior in mass transfer, conductivity, and the number of active sites. Suspended particles are introduced into the two-dimensional electro-permonosulfate system, where they are polarized to form microelectrodes under the action of an electric field and distributed throughout the system with hydraulic stirring. Each microelectrode surface can be activated with permonosulfate, thereby greatly expanding the electrocatalytic capacity. Summary of the invention
[0004] Based on the above content, the purpose of the present invention is to provide an application of a supported electrocatalyst in a three-dimensional electrode system to degrade Orange II dye wastewater. In the electro-supported electrocatalyst-permonosulfate three-dimensional electrode system of the present invention, the catalyst is polarized into a particle electrode, which can efficiently activate permonosulfate to produce active substances to degrade pollutants.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention discloses an application of a supported electrocatalyst in degrading orange II dye wastewater in a three-dimensional electrode system. Orange II dye wastewater, electrolyte and supported electrocatalyst are mixed to obtain a mixed solution. A cathode and an anode are inserted into the mixed solution, and then peroxymonosulfate is added and direct current is connected to achieve degradation of orange II.
[0007] The method for preparing the supported electrocatalyst comprises the following steps:
[0008] Adding iron salt and cobalt salt to the montmorillonite suspension, mixing evenly, to obtain a mixed suspension;
[0009] Adjusting the pH value of the mixture suspension, and then stirring the mixture to react to obtain a precursor solution;
[0010] The precursor solution is subjected to a hydrothermal reaction to obtain the supported electrocatalyst (hereinafter also referred to as cobalt ferrite / montmorillonite electrocatalyst).
[0011] The present invention discloses the following technical effects:
[0012] The present invention utilizes the respective characteristics of the electric-permonosulfate system and the transition metal-permonosulfate system, and converts the cobalt ferrite / montmorillonite electrocatalyst into a particle electrode through electric field polarization, which can accelerate the activation of permonosulfate to produce active substances. The electrode plate and the electrocatalyst jointly realize the rapid activation of permonosulfate to degrade dye molecules.
[0013] The preparation method of the cobalt ferrite / montmorillonite electrocatalyst of the present invention is simple. Cobalt ferrite with natural mineral montmorillonite as a carrier is selected as the catalyst. Montmorillonite as a carrier can reduce the agglomeration phenomenon in the process of metal oxide generation, disperse the catalytic sites, and reduce the specific gravity of the prepared electrocatalyst, which is beneficial to the suspension and dispersion in water during the catalytic process and expands the occurrence area of the advanced oxidation reaction. The cobalt-iron bimetallic oxide has better catalytic performance than the monometallic iron oxide. The interaction between Co and Fe in the spinel-type cobalt ferrite can effectively reduce the dissolution of metal ions in the catalytic process. The magnetic properties of the iron-cobalt oxide retain the possibility of magnetic separation recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 This is a scanning electron microscope image of pure cobalt ferrite, pure montmorillonite and cobalt ferrite / montmorillonite electrocatalyst in Example 1 of the present invention; wherein a is pure montmorillonite, b is cobalt ferrite, c is cobalt ferrite / montmorillonite electrocatalyst, d is Al, e is Si, f is Co, and g is Fe.
[0016] Figure 2Figure a is the X-ray diffraction pattern and b is the Fourier transform infrared spectrum of the pure cobalt ferrite, pure montmorillonite and cobalt ferrite / montmorillonite electrocatalyst in Example 1 of the present invention.
[0017] Figure 3 1 is the hysteresis loop diagram of the pure cobalt ferrite and cobalt ferrite / montmorillonite electrocatalysts in Example 1 of the present invention.
[0018] Figure 4 This is a schematic diagram of an apparatus for degrading Orange II using a cobalt ferrite / montmorillonite three-dimensional electrode catalytic system in Example 2 of the present invention, wherein: 1- a DC regulated power supply, 2- a mechanical stirrer, 3- a reaction vessel, 4- a flat electrode cathode, 5- a flat electrode anode, and 6- a water bath.
[0019] Figure 5 This is a graph showing the degradation curve of Orange II using the cobalt ferrite / montmorillonite three-dimensional electrode catalytic system to degrade Orange II in Example 2 of the present invention.
[0020] Figure 6 This is a graph showing the degradation curve of Orange II using the cobalt ferrite / montmorillonite three-dimensional electrode catalytic system to degrade Orange II under different operating conditions in Example 3 of the present invention, wherein a represents different electrocatalyst CFO / Mt dosage conditions, b represents different permonosulfate dosage conditions, and c represents different current density conditions.
[0021] Figure 7 This is a graph showing the degradation curve of Orange II obtained by using a cobalt ferrite / montmorillonite three-dimensional electrode catalytic system to degrade Orange II in the presence of different concentrations of chloride ions or phosphate ions in Example 4 of the present invention, wherein a represents different concentrations of chloride ions and b represents different concentrations of phosphate ions. DETAILED DESCRIPTION
[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0027] In the three-dimensional electrode system, common three-dimensional electrode materials are transition metals represented by Fe, Mn, Cu, Co and their oxides, but they inevitably have the defects of low catalytic efficiency and metal ion dissolution. 2+ , Mn 2+ 、Co 2+ 、Zn 2+ etc.) have a bimetallic coupling effect that a single metal oxide does not have, and have achieved satisfactory results in the field of persulfate activation. Among several MFe2O4, the unique advantage of cobalt ferrite CoFe2O4 is that in addition to high catalytic activity, the spinel configuration provides a stable structure, which effectively reduces the leaching rate of metal ions. Due to the huge surface energy during the metal crystallization process, agglomeration often occurs during the synthesis of spinel ferrite, resulting in a significant reduction in surface area and available sites. Loading oxides on a substrate with a stable structure is an effective strategy to improve particle dispersibility. Natural clay minerals are abundant in reserves, low in price, and have the characteristics of large specific surface area, rich pores, and high thermal stability, and can be used as adsorbents and catalyst carriers. Montmorillonite has strong hydrophilicity and high electronegativity, and the exchangeable cations between the layers provide conductivity, and the Lewis acid sites on the surface are beneficial to catalytic performance. Therefore, montmorillonite can be used as one of the good carriers of metal oxides. The present invention uses montmorillonite-loaded cobalt ferrite as a catalyst and is applied to the degradation of Orange II in a three-dimensional electrode system.
[0028] The present invention provides an application of a supported electrocatalyst in degrading orange II dye wastewater in a three-dimensional electrode system. Orange II dye wastewater, an electrolyte and a supported electrocatalyst are mixed to obtain a mixed solution. A cathode and an anode are inserted into the mixed solution, and then peroxymonosulfate is added and a direct current is connected to achieve degradation of Orange II.
[0029] The method for preparing the supported electrocatalyst comprises the following steps:
[0030] Adding iron salt and cobalt salt to the montmorillonite suspension, mixing evenly, to obtain a mixed suspension;
[0031] Adjusting the pH value of the mixture suspension, and then stirring the mixture to react to obtain a precursor solution;
[0032] The precursor solution is subjected to a hydrothermal reaction to obtain the supported electrocatalyst (ie, cobalt ferrite / montmorillonite electrocatalyst).
[0033] In the present invention, the preparation method of montmorillonite suspension can be selected from the technical means well known to those skilled in the art, for example: montmorillonite is mixed with water and stirred evenly; the specification of the montmorillonite is 500-2000 mesh, and the mass ratio of montmorillonite to water is (1-5):75.
[0034] In some embodiments of the present invention, the iron salt is at least one of iron nitrate, iron nitrate hydrate, iron chloride, iron chloride hydrate, iron sulfate and iron sulfate hydrate; the cobalt salt is at least one of cobalt nitrate, cobalt nitrate hydrate, cobalt chloride, cobalt chloride hydrate, cobalt sulfate and cobalt sulfate hydrate; the molar ratio of the iron element in the iron salt to the cobalt element in the cobalt salt is 2:1.
[0035] In the present invention, if the molar ratio of iron to cobalt is not 2:1, the generated catalyst is no longer cobalt ferrite, or is not pure enough cobalt ferrite. On the one hand, the catalytic effect cannot be guaranteed, and on the other hand, if the cobalt-iron ratio of 1:2 is lost, some metal elements will not be restrained by the Co-Fe interaction, and the metal ions in the effluent water after the catalyst is used will increase.
[0036] In some embodiments of the present invention, the mass ratio of the sum of the metal elements in the supported catalyst to montmorillonite is (14-35):100 (i.e., the mass ratio of the sum of the mass of the iron element and the cobalt element in the obtained cobalt ferrite / montmorillonite electrocatalyst to montmorillonite).
[0037] In some embodiments of the present invention, the pH value is 11.5; the stirring reaction temperature is room temperature, and the time is 1 hour. The present invention does not specifically limit the alkali solution used to adjust the pH, and any alkali solution well known to those skilled in the art can be selected, such as sodium hydroxide solution or potassium hydroxide solution.
[0038] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 180° C. and the time is 2 h.
[0039] The present invention obtains cobalt ferrite with abundant catalytic sites by strictly controlling the temperature and time of the hydrothermal reaction. If the parameters of the hydrothermal reaction are different from the above parameters, for example, hydrothermal reaction at 160° C. for 1.5 h, a large amount of iron salts and cobalt salts will not be able to generate cobalt ferrite through the hydrothermal reaction, resulting in loss of catalytic sites.
[0040] In some embodiments of the present invention, after the hydrothermal reaction is completed, the steps of cooling the reaction solution to room temperature, filtering and collecting the solid product, and washing and drying the solid product are also included.
[0041] When preparing the supported electrocatalyst, the present invention first prepares the montmorillonite carrier into a suspension, and then adds the metal salt so that the montmorillonite is sufficiently dispersed and can be evenly mixed with the iron and cobalt ions in the liquid phase; the pH is adjusted to be alkaline and the subsequent hydrothermal reaction can precipitate the metal ions on the surface of the montmorillonite and grow into cobalt ferrite crystals, thereby reducing the agglomeration of the metal during the growth process.
[0042] In some embodiments of the present invention, the electrolyte is sodium sulfate and / or potassium sulfate; the concentration of the electrolyte in the mixed solution is 10-50 mM; the amount of the supported electrocatalyst added to the mixed solution is 100-800 mg / L; and the amount of the peroxymonosulfate added is 200-500 μM.
[0043] In some embodiments of the present invention, the amount of the supported electrocatalyst added to the mixed solution is 200-800 mg / L; the amount of the peroxymonosulfate added is 300-500 μM.
[0044] In some embodiments of the present invention, the amount of the supported electrocatalyst added to the mixed solution is 400-800 mg / L; the amount of the peroxymonosulfate added is 400-500 μM.
[0045] In some embodiments of the present invention, the cathode and the anode are both flat electrodes, which are placed in parallel with a spacing of 4 cm. During the reaction, the flat electrodes are immersed in the reaction solution throughout the reaction process; the current density of the direct current is 3-9 mA / cm 2 .
[0046] In some embodiments of the present invention, the current density of the direct current is 5-9 mA / cm 2 .
[0047] In some embodiments of the present invention, the current density of the direct current is 7-9 mA / cm 2 .
[0048] In some embodiments of the present invention, the mixed solution further comprises chloride ions and / or phosphate ions. In the present invention, the presence of chloride ions and / or phosphate ions in the electrolytic system accelerates the degradation reaction of Orange II in the three-electrode system.
[0049] In the electro-permonosulfate system, cobalt ferrite / montmorillonite electrocatalyst (supported catalyst) is added to form a three-dimensional electrode system. The cobalt ferrite / montmorillonite electrocatalyst is stirred in the solution and is suspended. It is polarized into a particle electrode by the electric field. The flat electrode and the particle electrode jointly activate the permonosulfate to produce active species to degrade the dye molecules.
[0050] Most of the catalysts in the prior art are directly added to the water system to directly activate persulfate to degrade organic pollutants, and the field is limited to the scope of heterogeneous transition metal catalytic oxidation. The present invention prepares a catalyst suitable for an electrocatalytic system, which not only serves as a transition metal catalyst but also as a three-dimensional particle electrode, thereby improving the efficiency of the oxidant contacting with it, and also speeding up the rate of catalyzing the oxidant, alleviating the limitations of traditional heterogeneous catalytic oxidation; in addition, unlike heterogeneous catalytic oxidation, the catalyst does not need to consume persulfate to replenish the electron loss after the catalytic reaction, but obtains electrons by colliding with the cathode.
[0051] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0052] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0053] Example 1
[0054] The preparation of cobalt ferrite / montmorillonite electrocatalyst is as follows:
[0055] Add 75ml of deionized water to a 100ml beaker, weigh 1.000g of montmorillonite with a specification of 1000 mesh and add it to the beaker. Keep stirring magnetically at room temperature until there is no obvious stratification in the beaker after stopping stirring, and there is no gray-white large particle precipitation. At this time, it is considered that the montmorillonite has been fully dispersed and stirring is stopped. Weigh 0.5302g of cobalt acetate (Co(CH3COO)2, AR grade) and 1.724g of iron nitrate nonahydrate (Fe(NO3)3·9H2O, AR grade) and add them to the beaker at the same time. After magnetic stirring at room temperature for 1h, adjust the pH of the mixture suspension in the beaker to 11.5 with 1M sodium hydroxide solution. After continuing stirring for 1h, transfer the suspension to a 100ml hydrothermal reactor, place it in an electric heated forced air drying oven, and keep it at 180℃ for 2h. After natural cooling, the reactor was taken out. At this time, a brown-black solid precipitated in the reactor. The solid was filtered out, and the solid obtained in step three was washed alternately with anhydrous ethanol and deionized water for 3 times each, and the washed product was placed in a drying oven and dried at 60°C for 12 hours to obtain the cobalt ferrite / montmorillonite electrocatalyst, denoted as CFO / Mt.
[0056] This example also prepares cobalt ferrite without montmorillonite loading, which is denoted as CFO. The proportion and preparation process of CFO are the same as those of the cobalt ferrite / montmorillonite electrocatalyst, except that montmorillonite is not added.
[0057] In this example, some characterizations were performed on pure CFO, pure montmorillonite (denoted as Mt) and CFO / Mt.
[0058] The surface morphologies of pure CFO, pure Mt, and CFO / Mt, as well as the element distribution of CFO / Mt, were examined by scanning electron microscopy. Figure 1 As shown in (a), the unloaded montmorillonite sample exhibits a smooth and well-defined stacked lamellar structure. Figure 1 In figure b, the prepared pure CFO particles are spherical with a particle size of tens of nanometers. However, due to the strong surface energy during the synthesis process, the CFO nanoparticles self-aggregate together and eventually form micron-sized agglomerates, which reduces the surface area and reduces the catalytic effect compared to dispersed particles. Figure 1 The SEM image of CFO / Mt in c shows that the montmorillonite substrate still maintains a flaky structure after heat treatment, but the surface is no longer smooth, but has granular substances of varying sizes attached to the montmorillonite. The particle size of these surface particles is also about tens of nanometers, and they are identified as cobalt ferrite particles. The cobalt ferrite particles loaded on montmorillonite are significantly smaller and more uniform. Even if agglomeration occurs, the particle size of the agglomerates is still much smaller than that of pure CFO. Obviously, the cobalt ferrite particles synthesized by the hydrothermal method were successfully loaded onto montmorillonite, and the loading behavior significantly improved the agglomeration of cobalt ferrite. EDS technology was used to perform elemental analysis on CFO / Mt, such as Figure 1 In d and e, the dense distribution of Al and Si elements is a distinct feature of the mineral montmorillonite. Figure 1 Figures f and g show that Co and Fe elements are evenly distributed on the montmorillonite substrate, which also proves that cobalt ferrite does not undergo strong agglomeration on the montmorillonite substrate.
[0059] The crystal structures of pure Mt, pure CFO and CFO / Mt were compared by X-ray diffractometer. Figure 2 As shown in (a), in the range of 5-90°, the characteristic peaks of Mt at 5.95°, 17.71°, 19.86°, 26.82°, 29.57°, 35.00°, 54.18°, 61.90°, 73.30°, and 76.43° have very good correspondence with the crystal plane data of (001), (003), (100), (103), (005), (110), (210), (0010), (221), and (310) in the public file of the XRD database (JCPSD File NO.13-0135). The prepared pure CFO appeared at 18.47°, 30.24°, 35.67°, 43.31°, 57.23°, and 62.81°, corresponding to the (111), (220), (311), (400), (511), and (440) crystal planes (JCPSD File NO.03-0864). The XRD spectrum of pure CFO has no impurity peaks, proving that the CFO particles prepared in the above manner are of high purity and will not generate other substances. The two-phase composition of cobalt ferrite nanoparticles and montmorillonite was detected in the CFO / Mt composite, indicating that cobalt ferrite was successfully crystallized on the montmorillonite substrate. Unlike CFO and Mt, the peak intensity of CFO / Mt is inferior to the above two minerals, which indicates that the particle size of montmorillonite particles becomes smaller after heat treatment, and the crystallinity is reduced. Another evidence of the decrease in particle size is the relative broadening of the diffraction peak of CFO / Mt relative to that of pure CFO or pure Mt. The intensity of the diffraction peak of CFO / Mt at 7.16° is much smaller than that of pure CFO, which is attributed to the disappearance of interlayer water after heat treatment. In short, the XRD spectrum proves the good combination of CFO and Mt.
[0060] The surface groups of pure Mt, pure CFO and CFO / Mt were compared by Fourier transform infrared spectroscopy. The surface of montmorillonite is rich in hydroxyl groups, and the hydrophilicity provided by these hydroxyl groups can better enrich pollutants. At the same time, the presence of surface hydroxyl groups is also considered to be beneficial to persulfate activation. Figure 2 The strongest energy band of pure Mt shown in (b) is located at 1034 cm -1 This is the s produced by the plane vibration of the Si-O bond, 3440cm -1 The broad band is the OH stretching vibration of water molecules, 1639 cm -1The band is the bending vibration of OH, 3623cm -1 It is the stretching vibration of the OH group combined with cations such as Al. For pure CFO, the strongest band is located at 580cm -1 , which corresponds to the Fe-O bond, 3415 cm -1 The vibration at 580cm can be considered as a relatively weak surface hydroxyl group. In addition, there are no other obvious valleys, such as the vibration corresponding to the Co-O bond, which indicates that in the prepared CFO, Co exists in the form of tetrahedral Co(II). CFO / Mt has most of the chemical bond characteristics of pure CFO and pure Mt, and also has abundant surface hydroxyl groups of pure Mt. CFO / Mt has a peak at 580cm -1 Although it does not show the same strong energy band as pure CFO, the transmittance is increased compared with the pure Mt sample, indicating that Fe-O bonds still exist in CFO@Mt.
[0061] The hysteresis loops of pure CFO and CFO / Mt were tested by a hysteresis loop instrument. Figure 3 As shown in the figure, the saturation magnetization of pure CFO is 37.55emu / g, which has strong magnetism, while the saturation magnetization of CFO / Mt is reduced to 12.78emu / g due to the use of non-magnetic Mt as a substrate. CFO / Mt with relatively weak magnetism can be stirred and dispersed in aqueous solution without aggregation, but the residual magnetism still makes it possible to be magnetically separated and recovered.
[0062] Example 2
[0063] In this example, the CFO / Mt electrocatalyst prepared in Example 1 was used to construct an E-CFO / Mt-PMS three-dimensional electrode system to degrade the dye Orange II.
[0064] The schematic diagram of the experimental device is as follows: Figure 4 As shown in the figure, 1-DC regulated power supply, 2-mechanical stirrer, 3-reaction vessel, 4-plate electrode cathode, 5-plate electrode anode, 6-water bath. The reaction vessel used in this experiment is a quartz electrolytic cell with a volume of 250ml. The plate electrode cathode and the plate electrode anode are both platinum electrodes with an area of 3.5cm×5cm. The plate electrodes are placed in parallel with a spacing of 4cm. During the reaction, they are completely immersed in water and connected to the DC regulated power supply through wires. The water bath device uses a water bath pot to keep the water temperature constant during the reaction. The mechanical stirrer is used to dissolve the electrolyte, disperse the additives and keep the electrocatalyst suspended during the reaction. The stirring paddle size is 2.5cm wide.
[0065] Before the reaction, 200 ml of simulated dye wastewater was injected into the reactor. Orange II was used as the dye in this experiment with a concentration of 20 mg / L. 0.568 g of anhydrous sodium sulfate was added as electrolyte, stirred until dissolved, and then the electrocatalyst was added in proportion. Finally, persulfate was added to the reactor and the DC regulated power supply with pre-adjusted current was quickly turned on to start the reaction. At specific time points (0 min, 2.5 min, 5 min, 7.5 min, 10 min, 15 min, 20 min), 3 ml of water sample was taken out with a pipette, filtered with a 0.45 μm filter membrane, and then the water sample was transferred to a 5 ml centrifuge tube pre-added with 0.1 ml of 0.1 M sodium thiosulfate solution and shaken to stop the reaction. The concentration of Orange II in the water sample was measured using a UV-visible spectrophotometer.
[0066] Experimental conditions of this example: current density = 5 mA / cm 2 , electrocatalyst CFO / Mt dosage = 0.2 mM, permonosulfate dosage = 300 μM, Orange II concentration = 20 mg / L, sodium sulfate concentration = 20 mM, reaction temperature = 25°C, and the initial pH of the water sample was not adjusted.
[0067] Six groups of experiments with different systems were designed: ① electrolytic oxidation alone (E); ② adsorption alone (CFO / Mt); ③ electro-activated peroxymonosulfate catalysis (E-PMS); ④ electricity + electrocatalyst (E-CFO / Mt); ⑤ CFO / Mt activated peroxymonosulfate catalysis (CFO / Mt-PMS); ⑥ CFO / Mt three-dimensional electrode activated peroxymonosulfate system (E-CFO / Mt-PMS). The experimental results are shown in the figure. Figure 5 As shown. The removal efficiency of electrolysis alone is 8.1% within 20 minutes. Due to the hydrophilicity and large specific surface area of montmorillonite, CFO / Mt also has certain adsorption properties, and adsorption alone can also remove 3.7% of dye molecules. The degradation rate of the E-CFO / Mt system is 25.3%, which is higher than the sum of the degradation rates of the pure electrolysis and pure adsorption systems, indicating that CFO / Mt can form a micro-electrolysis cell under the action of the electric field, and serve as a three-dimensional electrode to improve the pollutant treatment efficiency. For the two binary activated permonosulfate systems, CFO / Mt-PMS and E-PMS, the degradation rates of Orange II within 20 minutes were 88.4% and 61.1%, respectively. The degradation efficiency is not high, indicating that the permonosulfate is not activated quickly. The above five systems still failed to achieve effective destruction of the molecular structure of Orange II. The E-CFO / Mt-PMS three-dimensional electrode system achieved a degradation rate of 98.5% after 20 minutes of reaction. Observation of the degradation curve shows that the degradation rate of Orange II in the E-CFO / Mt-PMS system is significantly improved compared with other systems.
[0068] Example 3
[0069] In this example, the E-CFO- / Mt-PMS three-dimensional electrode system was operated under different operating conditions to degrade the dye Orange II.
[0070] The operating method used in this experiment is consistent with that in Example 2. Unless otherwise specified, the experimental conditions are consistent with those in Example 2.
[0071] The experiments on the degradation of Orange II were carried out under different electrocatalyst CFO / Mt dosage conditions. Figure 6 As shown in a. In the E-CFO / Mt-PMS system, compared with the E-PMS system without added catalyst, the addition of 50mg / LCFO / Mt increased the degradation rate of Orange II from 56.6% to 84.3%. More CFO / Mt can provide a large number of active sites for the activation of PMS, thereby quickly generating free radicals. The three-dimensional electrode system can make these dispersed CFOs form micro-electrolytic cells, thereby promoting PMS activation. When CFO / Mt is greater than 100mg / L, further increasing the amount of electrocatalyst added increases the reaction rate of the system, but the degradation rate only increases by less than 1%.
[0072] Experiments were conducted to degrade Orange II under different persulfate dosages. Figure 6 As shown in b. When the PMS dosage is 100, 200, 300, 400, and 500 μM, the corresponding removal rates of Orange II are 69.1%, 90.7%, 96.2%, 98.6%, and 99.4%, respectively. The PMS dosage is in the range of 0 to 0.5 mM, which conforms to the rule that the higher the dosage, the higher the degradation efficiency. At this time, with the increase of the permonosulfate dosage, the permonosulfate concentration around the catalyst increases, and more permonosulfate is activated per unit time. The yield of active species increases accordingly, and the degradation rate of Orange II also increases accordingly.
[0073] Experiments were conducted to degrade Orange II under different current density conditions. The results are shown in Figure 6 As shown in c. The current density is 1, 3, 5, 7, 9 mA / cm 2 The removal rates of Orange II at 20 min were 60.0%, 79.1%, 91.3%, 98.5%, 99.1% and 99.0% respectively, and the rate constant increased from 4.95×10 -2 min -1 Increased to 23.85×10 -2 min -1On the one hand, the anode undergoes direct electrochemical oxidation reaction under the action of current. The increase in current density accelerates the transmission efficiency of electrons and improves the direct electro-oxidation capacity. On the other hand, the increase in current density increases the efficiency of activating PMS. In addition, the increase in current density will increase the voltage between the plates. The more charges accumulated on the plates, the easier it is to polarize CFO / Mt, making the metal valence cycle faster.
[0074] Example 4
[0075] In this example, the E-CFO- / Mt-PMS three-dimensional electrode system was operated under different chloride ion concentrations and different phosphate ion concentrations to degrade the dye Orange II.
[0076] In this experiment, sodium chloride is used as the salt corresponding to chloride ion, and disodium hydrogen phosphate is used as the salt corresponding to phosphate. Except for adding salt of corresponding concentration while adding electrolyte, other operation methods used are consistent with those in Example 2. Unless otherwise specified, other experimental conditions are consistent with those in Example 2.
[0077] Experiments were conducted to degrade Orange II under different chloride ion concentrations. The results were similar to Figure 7 As shown in a. When the chloride ion concentration is 0, 2.5, 5, and 10 mM, the corresponding removal rates of Orange II are 98.5%, 96.2%, 98.5%, and 97.5%, respectively, but the corresponding reaction rates are 0.146, 0.140, 0.239, and 0.172 min, respectively. -1 The presence of chloride ions accelerated the degradation reaction of Orange II in the E-CFO / Mt-PMS system.
[0078] Experiments were conducted to degrade Orange II under different chloride ion concentrations. The results were similar to Figure 7 As shown in b. When the phosphate concentrations were 0, 2.5, 5, and 10 mM, the corresponding removal rates of Orange II were 98.5%, 98.9%, 99.0%, and 99.1%, respectively, but the corresponding reaction rates were 0.146, 0.255, 0.307, and 0.343 min, respectively. -1 The presence of phosphate accelerated the degradation reaction of Orange II in the E-CFO / Mt-PMS system.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Application of a supported electrocatalyst in a three-dimensional electrode system for degrading orange II dye wastewater, characterized in that: The Orange II dye wastewater, electrolyte and supported electrocatalyst are mixed to obtain a mixed solution; a cathode and an anode are inserted into the mixed solution, and then peroxymonosulfate is added, and direct current is connected to achieve degradation of Orange II; The method for preparing the supported electrocatalyst comprises the following steps: Adding iron salt and cobalt salt to the montmorillonite suspension, mixing evenly, to obtain a mixed suspension; Adjusting the pH value of the mixture suspension, and then stirring the mixture to react to obtain a precursor solution; The precursor solution is subjected to a hydrothermal reaction to obtain the supported electrocatalyst.
2. The use of the supported electrocatalyst according to claim 1 in degrading Orange II dye wastewater in a three-dimensional electrode system, characterized in that: The iron salt is at least one of iron nitrate, iron nitrate hydrate, iron chloride, iron chloride hydrate, iron sulfate and iron sulfate hydrate; the cobalt salt is at least one of cobalt nitrate, cobalt nitrate hydrate, cobalt chloride, cobalt chloride hydrate, cobalt sulfate and cobalt sulfate hydrate; the molar ratio of the iron element in the iron salt to the cobalt element in the cobalt salt is 2:
1.
3. Use of the supported electrocatalyst according to claim 1 in degrading Orange II dye wastewater in a three-dimensional electrode system, characterized in that: In the supported electrocatalyst, the mass ratio of the sum of the metal elements to the montmorillonite is (14-35):
100.
4. Use of the supported electrocatalyst according to claim 1 in degrading Orange II dye wastewater in a three-dimensional electrode system, characterized in that: The pH value is 11.5; the stirring reaction temperature is room temperature and the time is 1 hour.
5. Use of the supported electrocatalyst according to claim 1 in degrading Orange II dye wastewater in a three-dimensional electrode system, characterized in that: The temperature of the hydrothermal reaction is 180° C. and the time is 2 h.
6. Use of the supported electrocatalyst according to claim 1 in degrading Orange II dye wastewater in a three-dimensional electrode system, characterized in that: After the hydrothermal reaction is completed, the steps of cooling the reaction solution to room temperature, filtering and collecting the solid product, and washing and drying the solid product are also included.
7. Use of the supported electrocatalyst according to claim 1 in degrading Orange II dye wastewater in a three-dimensional electrode system, characterized in that: The electrolyte is sodium sulfate and / or potassium sulfate; the concentration of the electrolyte in the mixed solution is 10-50 mM; the amount of the supported electrocatalyst added to the mixed solution is 100-800 mg / L; and the amount of the peroxymonosulfate added is 200-500 μM.
8. Degradation of Orange II dye wastewater in a three-dimensional electrode system using the supported electrocatalyst according to claim 1 The application is characterized in that The cathode and anode are both flat electrodes, and the flat electrodes are placed in parallel with a distance of 4 cm. During the reaction, the flat electrode is immersed in the reaction solution throughout the reaction; the current density of the direct current is 3-9mA / cm 2 .
Citation Information
Patent Citations
Activated carbon loaded iron-cobalt oxide catalyst and application thereof in degrading organic pollutants
CN102500376A
Application of bentonite-supported nanoscale zero-valent iron in three-dimensional electrode technology, paper-making wastewater treatment method and particle electrode preparation method
CN107032457A
Method for processing refractory wastewater by three-dimensional electrode coupled with oxidant
CN108928890A
Method for activating persulfate by catalytic particle electrode under driving of electric field, and application of method
CN109867334A
Method for treating landfill leachate biochemical tail water through three-dimensional electrode and persulfate advanced oxidation technology
CN113493238A